2022
DOI: 10.1108/vjikms-01-2022-0021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of knowledge management on innovative performance with the mediating effect of unlearning

Abstract: Purpose The purpose of this study is to examine the effect of knowledge management (KM) on innovative performance with the mediating effect of unlearning (UNL) in Iran Water Resources Management Company. Design/methodology/approach In terms of data collection, this study has elements of library study and field study. To collect the data, a researcher-made questionnaire with three subscales of KM, UNL and innovative performance was used. The population of this study was 800 employees of Iran Water Resources M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…If the knowledge management organization continues, this results in innovation throughout the organization. Consistent with the study of Samie & Jazghani, (2022), it was found that leaders can effectively use knowledge management to solve problems that arise in the organization and encourage employees to acquire new knowledge with the necessary thematic training to acquire new methods and processes for innovation. At the same time, information should be recorded or shared from successful and unsuccessful experiences in order to solve future problems leading to an organization of effective innovation.…”
Section: Knowledge Managementmentioning
confidence: 52%
See 1 more Smart Citation
“…If the knowledge management organization continues, this results in innovation throughout the organization. Consistent with the study of Samie & Jazghani, (2022), it was found that leaders can effectively use knowledge management to solve problems that arise in the organization and encourage employees to acquire new knowledge with the necessary thematic training to acquire new methods and processes for innovation. At the same time, information should be recorded or shared from successful and unsuccessful experiences in order to solve future problems leading to an organization of effective innovation.…”
Section: Knowledge Managementmentioning
confidence: 52%
“…Consistent with the study of Andersson et al (2023), it was found that entrepreneurs will achieve higher success if knowledge management is consistently put into practice to achieve the discovery of creativity to make the organization competitive. The study of Samie & Jazghani, (2022) found that organizational innovation can occur through knowledge management and knowledge sharing. They solve problems that will arise appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…Hierarchical component models technique (Ringle et al, 2022) was used to analyze the data using the partial least squares (PLS) method in the SmartPLS4 software environment. Unlike structural equation modeling approaches that are covariance-oriented, partial least squares modeling helps theory development in exploratory studies (Samie & Barati, 2023). In this method, theory development is done by focusing on explaining the variance of the dependent variable (Hair et al, 2016).…”
Section: Validity Conclusion and Discussion Interviewsmentioning
confidence: 99%